2005
DOI: 10.1103/physrevlett.95.040401
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond Double-Slit Experiment

Abstract: A new scheme for a double-slit experiment in the time domain is presented. Phase-stabilized few-cycle laser pulses open one to two windows ("slits") of attosecond duration for photoionization. Fringes in the angle-resolved energy spectrum of varying visibility depending on the degree of whichway information are observed. A situation in which one and the same electron encounters a single and a double slit at the same time is discussed. The investigation of the fringes makes possible interferometry on the attose… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
256
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(269 citation statements)
references
References 21 publications
12
256
0
1
Order By: Relevance
“…An additional interference structure is superposed on that described previously, which consists of circles centred at the origin, simply expressing energy conservation. This interference effect is very similar to that leading to electron peaks separated byhω, when atoms are ionized by intense laser pulses 23,24 . In addition, argon has three different initial states, 3p, m = 0,±1 and, for one-photon absorption, several possible final states with s or d symmetry.…”
mentioning
confidence: 52%
“…An additional interference structure is superposed on that described previously, which consists of circles centred at the origin, simply expressing energy conservation. This interference effect is very similar to that leading to electron peaks separated byhω, when atoms are ionized by intense laser pulses 23,24 . In addition, argon has three different initial states, 3p, m = 0,±1 and, for one-photon absorption, several possible final states with s or d symmetry.…”
mentioning
confidence: 52%
“…The precisely controllable CEP of a near-infrared driving waveform could be used to adjust both the ionization yield [28] in each field half-cycle and the classical excursion of the ionized electron in the continuum to generate, upon recombination with the parent ion, single or twin soft x-ray attosecond bursts of radiation near the cutoff of the emitted spectra. This first essential paradigm of attosecond control was followed by equally crisp demonstrations of strong-field controlled electron emission from atoms [29,30], their double ionization [31], the sub-cycle control and the dissociation in simple molecular species [32]. More recently, this paradigm was further extended to field sensitive control of chemical dynamics in more Figure 2.…”
Section: Attosecond Strong-field Physics In the Few-cycle Regimementioning
confidence: 99%
“…Theoretical calculations have shown that the (high energy) parts of PES coming from electron recollisions are more sensitive to CEP than the (low energy) parts from directly emitted electrons [15,12,16,17,18]. Experimentally, the dependence of high-energy PES on the CEP has been explored for atoms [13,19,20], dimer molecules [21], and nano-tips [22,23], providing challenging motivations for the theoretical investigations.…”
Section: Introductionmentioning
confidence: 99%